2020
DOI: 10.1155/2020/3415795
|View full text |Cite
|
Sign up to set email alerts
|

Husband Support Rises Women’s Awareness of Preconception Care in Northern Ethiopia

Abstract: Background. Preconception care (PCC) aims to improve pregnancy and health outcomes of mothers and their offspring. However, there is no adequate evidence of awareness on preconception care in Ethiopia. Therefore, the present study was performed to assess the level of awareness and associated factors of preconception care among currently delivered mothers. Method. A community-based cross-sectional study was conducted among 561 mothers in Northern Ethiopia. Data were collected using a pretested, structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Husbands had a great role in women's and children's health. Women who were able to decide themselves or jointly decide with their husbands were more likely to use preconception care than those who were not able to decide themselves [24,38]. However, in the current study, even though women were the major responsible individuals in fulfilling the family's needs, husbands were the main decision-makers in all activities and did not support women to obtain health services.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Husbands had a great role in women's and children's health. Women who were able to decide themselves or jointly decide with their husbands were more likely to use preconception care than those who were not able to decide themselves [24,38]. However, in the current study, even though women were the major responsible individuals in fulfilling the family's needs, husbands were the main decision-makers in all activities and did not support women to obtain health services.…”
Section: Discussioncontrasting
confidence: 66%
“…Thirty-eight women of reproductive age groups participated in the 4 focused group discussions. The mean age of the reproductive age group women was 29.67(range: [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The majority of the women were illiterate in terms of their educational status and multiparous in terms of parity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are appropriate interventional strategies to increase the knowledge and uptake of PCC in the community 18 , 19 , the current studies revealed women’s awareness about PCC and its utilization is low 20 , 21 . The knowledge level of PCC varies significantly from across the world 22 , 23 .…”
Section: Introductionmentioning
confidence: 70%
“…The sample size ranged from 142 women who reside in Addis Ababa [ 19 ] to 680 Western Shoa zone of Oromia [ 16 ]. Regarding geographical distribution of studies, four studies were from Oromia (30.7%) [ 16 , 18 , 23 , 27 ], four from Amhara (30.7%) [ 15 , 22 , 25 , 26 ], two from Tigray (15.4%) [ 21 , 24 ], two from (15.4%) SNNP[ 17 , 20 ] and one from AA (7.8%) [ 19 ]. Eleven of the included studies reported on knowledge[ 15 25 ], and six provided data on utilization of PCC[ 16 , 18 , 22 , 24 , 26 , 27 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%